1990
DOI: 10.1080/00071669008417280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dietary interaction of calcium and phosphorus in the high producing laying hen

Abstract: 1. In a 6 x 7 factorial experiment using 2688 22-week-old laying hens of the Lohmann-SL strain kept in cages (4 birds/cage), diets containing six calcium (20, 25, 30, 35, 40, 45 g calcium/kg) and seven phosphorus concentrations (3.2, 4.2, 5.2, 6.2, 7.2, 8.2, 16.2 g total phosphorus/kg (Pt)) were combined orthogonally. The resulting 42 treatments were replicated 8 times so that a replicate consisted of a double cage of 2 x 4 hens. The experiment lasted 40 weeks (10 x 28 days). 2. The experimental diets, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…(1992) who reported that the extra calcium feeding increased shell weight. Our results with respect to egg production and FE obtained from the 1.50 g marble added group are in line with Hartel (1990) who showed that high levels of dietary calcium (3.5–4.5%) slightly decreased egg mass. The high dose of marble (1.50 g) in the present study decreased egg production possibly because of disruption to Ca : P ratios, and/or dilution of protein and energy in the complete diet which had a fixed Ca : P ratio.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…(1992) who reported that the extra calcium feeding increased shell weight. Our results with respect to egg production and FE obtained from the 1.50 g marble added group are in line with Hartel (1990) who showed that high levels of dietary calcium (3.5–4.5%) slightly decreased egg mass. The high dose of marble (1.50 g) in the present study decreased egg production possibly because of disruption to Ca : P ratios, and/or dilution of protein and energy in the complete diet which had a fixed Ca : P ratio.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies report that high levels of dietary calcium do not affect eggshell breaking strength, thickness (Hartel 1990) or quality (Keshavarz 1986), and that a step‐up phase feeding system (3.5, 4.5, 5.5% Ca) is also without effect on eggshell quality (Keshavarz & Nakajima 1993). However, in the present study, the 0.75 and 1.5 g marble addition to complete diet improved eggshell quality (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dietary level of calcium affects the feed and energy intake of hens, as, for example, Härtel (1990) and Roland and Bryant (1994) demonstrated. Feed intakes lower in FC than in CC have been reported by Elson and Croxall (2006) and Valkonen et al (2006), whereas others (Hetland et al, 2004) have reported higher feed intakes in FC than in CC.…”
Section: Introductionmentioning
confidence: 99%